The right of emphyteusis in the history of the Russian state (the late 15th – early 20th century) - A. A. Sapunkov; N. A. Sapunkov (Правоприменение)
The subject. The law of emphyteusis was studied in the Russian Empire in the middle of 19th – beginning of 20th century due to practical significance. The interest in this subject began to revive at the beginning of the 21st century, the first few publications appeared, but they were mostly replicas of Imperial period studies. The law of emphyteusis in Russia before the middle of the 19th century is not researched sufficiently. The purpose of the study is to confirm or disprove hypothesis that the law of emphyteusis was initially implemented in the system of Russian law as a legislative institution, but since the middle of the 19th century it has acquired the status of a local legal custom. The Russian state, having preserved the former system of civil law (the Lithuanian Statute) in the Western lands annexed from Lithuania and Poland, created the basis for the formation of a different system of legal awareness among a part of the population, thereby consolidating the dichotomy of the Empire and the Western provinces. Since the issue of land ownership is a key issue for feudal society, the law of emphyteusis is the most striking example of the split in the unity of the legal system of the Russian state. The methodology. The study is based on a combination of formal-legal and historical-legal methods: the methods of historicism, synchronous and diachronic comparison allow us to get an idea of the socio-political conditions in which the law of emphyteusis was formed and functioned. The main results, scope of application. The institute of emphyteusis (Latin – сensus, German – zins, Polish – czynsz) was formed on the basis of the reception of Roman and Byzantine law in the feudal law of a number of European States. Emphyteusis comes to the PolishLithuanian lands as an element of German law. The article describes the socio-political processes in the territories annexed by Russia from the Polish-Lithuanian Commonwealth, where the right of emphyteusis was preserved in the middle of 17th - first half of the 19th century as a local civil law under the Lithuanian Statute system. After the abolition of the Statute of Lithuania (1840) an emphyteusis preserved as a regional legal custom. The analysis of legislation and law enforcement practice on the issue of emphyteusis on the borderlands of the Russian state is carried out. The ineffectiveness of the state policy on the elimination of emphyteusis is noted. Conclusions. The revealed specifics of the development of emphyteusis in the Russian Empire are extremely poorly studied, although they indicate far-reaching consequences in the system of forming the legal consciousness of Russian, Ukrainian, Belarusian, Jewish (Ashkenazi) and other peoples.